COMPARISON OF LATEX AND SILICON INDWELLING CATHETER IN TERMS OF RATE OF BACTERIAL COLONIZATION IN MALES WITH ACUTE URINARY RETENTION AT 5TH DAY OF CATHETERIZATION - Aurangzeb,; Mubashar Abrar,; Naveed Ahmad Wattoo,; Moin Anwar,; Fatima Ashraf,; Kamran Liaqat,; Rehan Idrees,; Ayesha Mahnoor,; Muhammad Muneeb, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Urinary catheterization is considered as one of the most common, frequently performed and basic skill in patient care while catheter associated urinary tract infections (CAUTI) in the most common nosocomial infection. Catheter material plays an important part in terms of infection and bacterial colonization. With this study, we aim to compare the rate of bacterial colonization in two most commonly used catheter type; Latex and Silicone indwelling catheters in males with acute urinary retention. Methods: This 2-arm randomized control trial was conducted in Allied Hospital Faisalabad over the period of 2 months, from Jan 2023 to February 2023. Seventy-two male patients with acute urinary retention were included in this study. Patients were divided into 2 groups. Intervention groups was catheterized with silicon indwelling catheter and control groups was catheterized with latex indwelling catheter. Patients were discharged without antibiotics prescription and at 5th day catheter was removed and tip of catheter was sent for culture and sensitivity. Result was received on OPD basis and added in the record. Results: In comparison to the latex catheter, the silicone catheter showed significantly reduced bacterial colonization. In the Silicon indwelling catheter group, out of 36, 8 patients catheters showed bacterial growth while 28 exhibited no growth. In the Latex indwelling catheter group, out of 36, 17 patients catheters showed bacterial growth while 19 exhibited no growth. Conclusion: The findings showed that, on the fifth day of catheterization, silicone indwelling catheters significantly reduced the rate of bacterial colonization when compared to latex indwelling catheters.